2014 IEEE International Conference on Mechatronics and Automation 2014
DOI: 10.1109/icma.2014.6885750
|View full text |Cite
|
Sign up to set email alerts
|

Ride control method of wave-piercing catamaran with T-foil and flaps

Abstract: A T-foil is installed at the bow and two flaps are installed at the stern transom to control the motion of a wavepiercing catamaran. The T-foil and flaps are controlled by a ride controller, so as to smoothen pitch and heave motions of the ship effectively. Firstly, the mathematical model to describe the ship's vertical motion is constructed, and its coefficients are established from the Strip Theory. Then, the hydrodynamic characteristics of the T-foil and transom flaps are analyzed by employing CFD methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…They reported a 20% reduction of MSI in 3 m waves at the fore location of the vessel using a linear control RCS with medium slew rate, compared with the no RCS case. 5 Similarly, Zhang et al 45 built a mathematical model of a 90 m WPC travelling at 40 knots based on strip theory, and estimated the reduction of MSI by comparing the WPC fitted with active T-foil and tabs, and without RCS. It is worth mentioning that though the predicted MSI on the centreline reduced from 19% to 5%, the estimation method of MSI they used was different from the method included in the ISO standard 2631-1.…”
Section: Wave-piercing Catamarans (Wpcs)mentioning
confidence: 99%
“…They reported a 20% reduction of MSI in 3 m waves at the fore location of the vessel using a linear control RCS with medium slew rate, compared with the no RCS case. 5 Similarly, Zhang et al 45 built a mathematical model of a 90 m WPC travelling at 40 knots based on strip theory, and estimated the reduction of MSI by comparing the WPC fitted with active T-foil and tabs, and without RCS. It is worth mentioning that though the predicted MSI on the centreline reduced from 19% to 5%, the estimation method of MSI they used was different from the method included in the ISO standard 2631-1.…”
Section: Wave-piercing Catamarans (Wpcs)mentioning
confidence: 99%
“…On a different note, Zhang et al (2014) implemented Ride Control Systems with a Linear-Quadratic-Gaussian controller in a 90 m 2D + t model of a WPC to reduce vertical motion. Their study demonstrated the feasibility of reducing heave motion (about 20%) and pitch motion (about 60%) with RCS in Douglas Sea states 4 to 6, while advancing at a speed of 40 knots.…”
Section: Introductionmentioning
confidence: 99%
“…With this study, a general neuro-fuzzy model that can be used for any condition and control method has been obtained. Zhang et al (2014) used the LQG control method to smooth the vertical motions of a catamaran. In their work, they designed a ride control system adopting the LQG optimum control theory and analyzed the motions of a catamaran in different sea states.…”
Section: Introductionmentioning
confidence: 99%